Analysis of Government Communication Towards the Implementation of the Sp4n Lapor Application in the Communication and Informatics Service - Daud Riba; Yusmanizar Yusmanizar; Muhammad Yusuf AR (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study examines how government communication influences the implementation of the National Public Service Complaint Management System – People’s Online Aspirations and Complaints Service (SP4N-LAPOR) at the Department of Communication and Informatics of Biak Numfor Regency. The analysis is based on George C. Edward III’s policy implementation model, focusing on four aspects: communication, resources, disposition, and bureaucratic structure. Using a descriptive qualitative method, data were gathered through interviews, observations, and documentation. The results show that while SP4N-LAPOR has been implemented, it has yet to reach optimal performance. Public outreach remains limited, inter-agency coordination is not fully effective, supporting facilities and technical training for administrators are inadequate, and the application of Standard Operating Procedures (SOPs) is inconsistent. Other obstacles include low digital literacy among the community, budget constraints, and the archipelagic geography that hinders service coverage. The study recommends enhancing public outreach, providing more training, increasing resources, and strengthening cross-agency coordination to ensure SP4N-LAPOR operates more effectively in Biak Numfor.